Regional perfusion for soft tissue sarcomas and malignant melanomas - Stehlin (Jr.), John S. (Congresos Uruguayos de Cirugía, 1965)
Experience with perfusions for soft tissue sarcomas and malignant melanomas arising on the extremities of patients observed at the M. D. Anderson Hospital and Tumor Institute has convinced us that this procedure has real merit as a treatment for these types of tumors.